Alpenpfeifhase-drawing - Gustav Mützel (Wikimedia Commons, 1927)
Notice iconographique issue de Wikimedia Commons. Titre: Alpenpfeifhase-drawing. Alpine pika (Ochotona alpina). Size: 5.2 x 3.1 in² (13.2 x 7.9 cm²).
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons